Race and Ethnic and Sex Differences in Rhythm Control Treatment of Incident Atrial Fibrillation - Jackson LR II; Friedman DJ; Francis DM; Maccioni S; Thomas VC; Coplan P; Khanna R; Wong C; Rahai N; Piccini JP (Dove Medical Press, 2023)
Larry R Jackson II,1 Daniel J Friedman,1 Diane M Francis,2 Sonia Maccioni,2 Vincent C Thomas,3 Paul Coplan,4 Rahul Khanna,4 Charlene Wong,4 Neloufar Rahai,4 Jonathan P Piccini1 1Division of Cardiology, Duke University Medical Center & Duke Clinical Research Institute, Durham, NC, USA; 2Health Economics and Market Access, Johnson & Johnson Medical Devices, Irvine, CA, USA; 3Medical Safety, Biosense Webster, Irvine, CA, USA; 4Medical Device Epidemiology and Real-World Data Sciences, Johnson & Johnson, New Brunswick, NJ, USACorrespondence: Larry R Jackson II, Duke Clinical Research Institute, 300 W. Morgan Street, Durham, NC, 27701, USA, Tel +1 919-684-9940, Email larry.jackson@duke.eduBackground: Atrial fibrillation (AF) is associated with considerable morbidity and mortality. Timely management and treatment is critical in alleviating AF disease burden. Variation in treatment by race and ethnic and sex could lead to inequities in health outcomes.Objective: To identify racial and ethnic and sex differences in rhythm treatment for patients with incident AF.Methods: Using 2010- 2019 Optum Clinformatics database, an administrative claims data for commercially insured patients in the United States (US), incident AF patients ≥ 20 years old who were continuously enrolled 12-months pre- and post-index diagnosis were identified. Rhythm control treatment (ablation, antiarrhythmic drugs [AAD], and cardioversion) for AF were compared by patient race and ethnicity (Asian, Hispanic, Black vs White) and sex (female vs male). Multivariable regression analysis was used to examine the relationship of race and ethnicity and sex with rhythm control AF treatment.Results: A total of 77,932 patients were identified with incident AF. Black and Hispanic female patients had the highest CHA2DS2VASc scores (4.3 ± 1.8) and Elixhauser scores (4.1 ± 2.8 and 4.0 ± 6.7), respectively. Black males were less likely to receive AAD treatment (adjusted odds ratio [aOR] 0.87; 95% confidence interval [CI], 0.79- 0.96) or ablation (aOR, 0.72; 95% CI, 0.58- 0.90). Compared to White males, all groups had lower likelihood of receiving cardioversion with Asian females having the lowest [aOR, 0.48; 95% CI, (0.37- 0.63)].Conclusion: Black patients were less likely to receive pharmacologic and procedural rhythm control therapies. Further research is needed to understand the drivers of undertreatment among racial and ethnic groups and females with AF.Keywords: race, sex, atrial fibrillation, catheter ablation